IMPLEMENTASI MANDATORY AKRUAL BASIS TERHADAP SISTEM INFORMASI PENGELOLAAN KEUANGAN NEGARA - Gita Nurdiniati; Nila Jania Saptianty; Didu Wahyudi (Universitas Bandar Lampung (UBL), 2022)
The government accounting information system was developed on an accrual basis. Many obstacles in the application of the accrual basis are faced by the state financial management apparatus. Broadly speaking, these constraints are categorized into two factors, namely the preparation of information system technology and the operators who run the system. Information technology is an important tool that supports organizational effectiveness and efficiency in supporting good state financial governance. Literature study with the selection of topics relevant to the current conditions of implementing SAKTI 2022. The journal publications used are those published by universities and the Ministry of Finance. The keywords for journal search are